The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1039/d0cc07405e
|View full text |Cite
|
Sign up to set email alerts
|

CO release from Mn(i)-based photoCORMs with single photons in the phototherapeutic region

Abstract: New Mn(i)-based photoCORMs with a fac-{Mn(CO)3} moiety exhibit facile CO release upon simple exposure to light within the phototherapeutic region (no two photon excitation required).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…The bond angle N(1)-Mn-O (4) = 78.3(1) , N(1)-Mn-C(2) = 171.1(2) and O(4)-Mn-C(3) = 174.5(2) deviate considerably from that of an ideal octahedral geometry. Among the three Mn-C (CO) bonds, the one trans to Br is the longest (1.840(7) Å) and subsequently the axial CO has the shortest bond length (1.05(1) Å), this is in agreement with those reported by Mascharak et al [40,43] The two CO groups trans to the azachalcone ligand have slightly different bond lengths. The CO which is trans to the N1 atom has a bond length of 1.131(6) Å while the one which is trans to O(4) is 1.140(6) Å.…”
Section: Structural Analysis Of 4chclsupporting
confidence: 89%
See 1 more Smart Citation
“…The bond angle N(1)-Mn-O (4) = 78.3(1) , N(1)-Mn-C(2) = 171.1(2) and O(4)-Mn-C(3) = 174.5(2) deviate considerably from that of an ideal octahedral geometry. Among the three Mn-C (CO) bonds, the one trans to Br is the longest (1.840(7) Å) and subsequently the axial CO has the shortest bond length (1.05(1) Å), this is in agreement with those reported by Mascharak et al [40,43] The two CO groups trans to the azachalcone ligand have slightly different bond lengths. The CO which is trans to the N1 atom has a bond length of 1.131(6) Å while the one which is trans to O(4) is 1.140(6) Å.…”
Section: Structural Analysis Of 4chclsupporting
confidence: 89%
“…[ 25,35,39–42 ] Recently, Mascharak et al reported photoCORMs that have MLCTs in the 750‐ to 785‐nm range, the highest reported so far. [ 43 ] Among these, the complexes containing N and O as the chelating atoms such as acenaphthylen‐1‐one and quinolone‐8‐one exhibited MLCT at 630 and 785 nm, respectively. Thus, it can be concluded that even if the ligating atoms are same, the type of ligand framework can immensely affect the position of the MLCT.…”
Section: Introductionmentioning
confidence: 99%
“…One of the main challenges in designing an efficient photoCORM is activation by light in the phototherapeutic window (600–950 nm). To date, various strategies, including ancillary ligand modifications, , multiphoton excitation, , mixing with a triplet-state photosensitizer, quantum dots, upconverting nanoparticles, or as previously reported by our group, coupling with a visible light absorbing metal complex, and so forth, have been employed to activate the photo-CO dissociation under visible and NIR irradiation. Alternatively, the use of dye photosensitizers as light-harvesting components of the design allows for visible light-activated photoCORMs …”
Section: Introductionmentioning
confidence: 99%
“…In a similar manner, carbon monoxide (CO), although mostly known for its strong toxicity due to strong binding to hemoglobine, was recently discovered to be produced endogenously in small amounts and responsible, similarly to NO, for a variety of physiological effects [19] . This has also triggered the development of targeted CO photoreleasing compounds ( photoCORMs ) [20–27] …”
Section: Introductionmentioning
confidence: 99%
“… [19] This has also triggered the development of targeted CO photoreleasing compounds ( photoCORMs ). [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]…”
Section: Introductionmentioning
confidence: 99%